Cost-Effectiveness Analysis Of Metformin Use In Type 2 Diabetes Mellitus Patients In Hospitals: A Systematic Literature Review - Wahyu Kurniawan; Thinni Nurul Rochmah (CV. AFDIFAL MAJU BERKAH, 2026)
Type 2 diabetes mellitus (T2DM) places a significant economic burden on Indonesia, necessitating the selection of cost-effective pharmacological therapies. Metformin has long been recommended as first-line therapy, but evidence of its cost-effectiveness across Indonesian hospitals remains fragmented and methodologically diverse. This study aimed to conduct a systematic review and synthesize evidence regarding the cost-effectiveness of metformin use in T2DM patients in Indonesian hospitals. The study used a systematic literature review design based on the PRISMA framework. Articles published since 2020 and obtained from Google Scholar, PubMed, and Publish or Perish were assessed using the PICO criteria (Population: T2DM patients in hospital; Intervention: metformin; other antidiabetic therapies; Outcome: cost-effectiveness). In total, six national studies were selected, covering both inpatient and outpatient settings. Data were extracted descriptively, while cost-effectiveness results (primarily the Average Cost-Effectiveness Ratio/ACER) were analyzed narratively. Across all reviewed studies, metformin consistently demonstrated lower ACER values ​​than comparator therapies (e.g., glibenclamide, glimepiride, gliquidone, and acarbose-based combinations), suggesting better cost-efficiency with equivalent or higher clinical effectiveness. Conclusion: Metformin is a cost-effective first-line therapy for T2DM patients in Indonesian hospitals, making it worthy of being maintained as the primary choice in clinical practice and hospital formularies.